Ce and P123 modified layered double hydroxide (LDH) composite for the synthesis of polypropylene glycol monomethyl ether - Cao, Xiaoyan; Kong, Lingxin; Gu, Zhenggui; Xu, Xiao (RSC advances, 2022)
The application of recyclable heterogeneous catalysts in the production of polypropylene glycol monomethyl ether (MPPG) is of great significance to the green chemical industry. In this study, the CeO 2 /MgAl-LDH(P123) composite was prepared using a nucleation/crystallization isolation method and aqueous reconstruction method, and CeO 2 /MgAl-LDO(P123) solid base catalyst was prepared by calcination with it as precursor. Thereafter, the morphology, crystal structure, functional group, and thermal stability of the catalyst were characterized using scanning electron microscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, Brunauer-Emmett-Teller analysis, temperature-programmed desorption of carbon dioxide, thermogravimetry, and X-ray photoelectron spectroscopy. The results showed that the catalyst had a larger specific surface area, pore size and pore volume and more basic sites, providing sufficient catalytic activity for the polymerization process. The experimental results for the fabrication of MPPG using CeO 2 /MgAl-LDO(P123) as catalyst and methanol and propylene oxide as reaction raw materials showed that the conversion of propylene oxide reached 92.04% and the molecular weight of MPPG was 405 under the optimal reaction conditions. Moreover, the conversion of propylene oxide was maintained above 83.69% after the catalyst was reused six times. This study offers a new prospect for the green synthesis of MPPG products. The application of recyclable heterogeneous catalysts in the production of polypropylene glycol monomethyl ether (MPPG) is of great significance to the green chemical industry.